Two inhibitory control training interventions designed to improve eating behaviour and determine mechanisms of change - Allom, Vanessa; Mullan, Barbara (Academic Press, 2015)
Inhibitory control training has been shown to influence eating behaviour in the laboratory; however, the reliability of these effects is not yet established outside the laboratory, nor are the mechanisms responsible for change in behaviour. Two online Stop-Signal Task training interventions were conducted to address these points. In Study 1, 72 participants completed baseline and follow-up measures of inhibitory control, self-regulatory depletion, fat intake and body-mass index. Participants were randomly assigned to complete one of three Stop-Signal Tasks daily for ten days: food-specific inhibition - inhibition in response to unhealthy food stimuli only, general inhibition - inhibition was not contingent on type of stimuli, and control - no inhibition. While fat intake did not decrease, body-mass index decreased in the food-specific condition and change in this outcome was mediated by changes in vulnerability to depletion. In Study 2, the reliability and longevity of these effects were tested by replicating the intervention with a third measurement time-point. Seventy participants completed baseline, post-intervention and follow-up measures. While inhibitory control and vulnerability to depletion improved in both training conditions post-intervention, eating behaviour and body-mass index did not. Further, improvements in self-regulatory outcomes were not maintained at follow-up. It appears that while the training paradigm employed in the current studies may improve self-regulatory outcomes, it may not necessarily improve health outcomes. It is suggested that this may be due to the task parameters, and that a training paradigm that utilises a higher proportion of stop-signals may be necessary to change behaviour. In addition, improvements in self-regulation do not appear to persist over time. These findings further current conceptualisations of the nature of self-regulation and have implications for the efficacy of online interventions designed to improve eating behaviour.